Electroacupuncture Therapy Ameliorates Motor Dysfunction via Brain-Derived Neurotrophic Factor and Glial Cell Line-Derived Neurotrophic Factor in a Mouse Model of Parkinson's Disease. (23rd October 2019) - Pak, Malk Eun; Ahn, Sung Min; Jung, Da Hee; Lee, Hong Ju; Ha, Ki Tae; Shin, Hwa Kyoung; Choi, Byung Tae
Abstract: Parkinson's disease (PD) is characterized by dopaminergic neuron loss in the substantia nigra. However, specific sensory stimulation via electroacupuncture (EA) therapy may attenuate this loss by promoting the expression of endogenous neurotrophic factors in a manner similar to physical therapy. We investigated the potential protective effects of EA on dopaminergic neurons in a mouse model of PD and whether these effects are associated with the promotion of endogenous brain-derived neurotrophic factor (BDNF) and glial cell line-derived neurotrophic factor (GDNF). Mouse models of PD were generated using 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) and 6-hydroxydopamine. Motor performance was assessed using behavioral tests, and Western blot experiments, enzyme-linked immunosorbent assays (ELISAs), and immunohistochemical assays were performed. In both mouse models, EA treatment ameliorated motor impairments and dopaminergic neuron loss; these changes were accompanied by increases in BDNF and GDNF. In the MPTP group, EA treatment improved motor dysfunction by attenuating dopaminergic neuron loss in the substantia nigra, similar to the effects of levodopa. EA treatment significantly upregulated BDNF and GDNF expression in both the substantia nigra and striatum. Moreover, EA treatment induced the expression of cAMP response element binding protein (CREB) as well as Akt and Pitx3 in dopaminergic neurons in the substantia nigra. However, levodopa treatment did not induce BDNF/GDNF activation or related signaling factors. Thus, EA therapy may exert protective effects on dopaminergic neurons by upregulating the expression of BDNF, GDNF, and related signaling factors, thereby improving motor function. Hence, EA may represent an effective adjuvant therapy for motor deficits in patients with PD.